A method of sub-aperture slope stitching for testing flat element based on phase measuring deflectometry. (November 2018) - Chen, Pengyu; Li, Dahai; Wang, Qionghua; Li, Lei; Xu, Kaiyuan; Zhao, Jiangang; Wang, Ruiyang
Highlights: A method of sub-aperture slope stitching based on PMD is proposed to test large-size optical flat. Multi-camera slope stitching model and corresponding algorithm in PMD are proposed. What aberrations will be brought into the measurement result due to relative errors has been analyzed. This method can test large-size optical flat with a high accuracy and cost-effective. The proposed test system is very simple and easy to follow, which can be used in on-line test. Abstract: Phase measuring deflectometry (PMD), which is a slope measurement technique based on fringe reflection, is a contact-free, high dynamic range, full field metrological method. In this paper, the method of sub-aperture slope stitching based on PMD is proposed for testing large-size optical flat, and a two-camera stitching test system is built in our lab to verify this suggestion. We discuss in detail what aberrations are brought into the measurement result due to the errors of alignment and calibration between the reference camera and the others. In our test system, all cameras are attached around the LCD display to enable the different cameras 'see' the different areas of a test component at the same time without moving any devices or the test component. Next, based on the measurement result of multiple cameras, the full global slope data are obtained with a minimum stitching error by using our stitching model and corresponding algorithm proposed in this paper. The stitched slope data are integrated to obtain the figure of the test surface. The results of simulation experiment show this paper's stitching model is superior to traditional stitching model and algorithm in PMD. Finally, we test an optical flat with a size of 152.6 mm in diameter using our method. The final measurement result shows that our test is nearly consistent with the result measured by Fizeau interferometer. It reveals that this method has advantages in testing large-size optical flat with a high-accuracy and cost-effective.